2021
DOI: 10.21873/invivo.12549
|View full text |Cite
|
Sign up to set email alerts
|

Combined Therapy of ATRA and Imatinib Mesylate Decreases BCR-ABL and ABCB1/MDR1 Expression Through Cellular Differentiation in a Chronic Myeloid Leukemia Model

Abstract: Background/Aim: Chronic Myeloid Leukemia (CML) is a clonal myeloproliferative disease, and a major challenge for the eradication of CML is to understand the cause of the permanence of minimal residual disease (DRM). This work aimed to induce the maturation of leukemic stem cells with All-trans-retinoic acid (ATRA), making them sensitive to treatment with Imatinib (IM). Materials and Methods: K562 cells were treated with IM and with the combined therapy of ATRA together with IM for 48 and 72 h. The expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…At present, the treatment of leukemia is mainly based on the combination of chemotherapy and targeted therapy, but there are obvious side effects and a high recurrence rate. The differentiation induction therapy represented by all-trans retinoic acid is one of the best methods for the treatment of leukemia (9)(10)(11); in that, the leukemia cells are induced to differentiate into mature promyelocytes by all trans retinoic acid (ATRA) and their malignant proliferation is inhibited. It is precisely because of this selective effect on leukemia cells that it does not affect normal hematopoietic and immune functions, making it a research hotspot (12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the treatment of leukemia is mainly based on the combination of chemotherapy and targeted therapy, but there are obvious side effects and a high recurrence rate. The differentiation induction therapy represented by all-trans retinoic acid is one of the best methods for the treatment of leukemia (9)(10)(11); in that, the leukemia cells are induced to differentiate into mature promyelocytes by all trans retinoic acid (ATRA) and their malignant proliferation is inhibited. It is precisely because of this selective effect on leukemia cells that it does not affect normal hematopoietic and immune functions, making it a research hotspot (12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with traditional chemotherapy, induced differentiation therapy has become an ideal method for the treatment of leukemia due to its non-toxic side effects (7,8). However, so far, only patients with acute promyelocytic leukemia could get the complete remission induced by differentiation-inducing drugs such as all-trans retinoic acid; other types of leukemia have not benefited from them (9)(10)(11). Therefore, it is necessary to actively explore new intervention targets and corresponding targeted drugs on the basis of in-depth exploration of the key mechanisms of leukemia differentiation disorders.…”
Section: Mir-let-7c-3p Targeting On Egr-1 Contributes To the Committe...mentioning
confidence: 99%
“…ATRA reduces the DNA damage repairing and inhibits the acquiring of Bcr/Abl1 mutation during the treatment of CML, consequently reducing the adaptive drug resistance in CML [48,49] . These results further veri ed the reliability of our previous ndings on KIAA1429, and suggested that inhibiting KIAA1429 could be a potential effective target for treating CML-BC or such with drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of MDR1 causes cross-resistance to many anticancer agents and thus could impact other available therapy options [ 23 ]. Therefore, researchers endeavor to develop novel pharmacological approaches to prevent or to overcome MDR1 in CML [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%